Aspergillus Galactomannan Enzyme Immunoassay and Quantitative PCR for Diagnosis of Invasive Aspergillosis with Bronchoalveolar Lavage Fluid - Musher, Benjamin (American Society for Microbiology, 2004)
Invasive pulmonary aspergillosis (IPA) is frequent and often fatal in hematopoietic stem cell transplant patients. Diagnosis requires microbiological or histopathologic demonstration of the organism in tissues; however, cultivation of Aspergillus species from respiratory secretions has low diagnostic sensitivity. Assays to detect Aspergillus antigen or DNA in bronchoalveolar lavage (BAL) fluid could facilitate earlier diagnosis, thereby guiding optimal therapy and obviating the need for additional costly and potentially morbid diagnostic evaluation. We evaluated the performance of a galactomannan enzyme immunoassay (GM EIA; Bio-Rad) by using a range of index cutoffs to define positivity and a quantitative PCR (qPCR) assay for the detection of Aspergillus species from BAL samples of patients with proven and probable IPA (case patients; n = 49) and without IPA (control patients; n = 50). The sensitivity of the GM EIA was 61% with an index cutoff of 1.0 and 76% with an index cutoff of 0.5; the corresponding specificities were 98 and 94%, respectively. The sensitivity and specificity of qPCR assay were 67 and 100%, respectively. The sensitivity with 22 culture-negative BAL specimens from patients with IPA was 41% for GM EIA with an index cutoff of 1.0, 59% for GM EIA with an index cutoff of 0.5, and 36% for qPCR assay. GM EIA indices and DNA quantities corresponded to BAL fungal burdens, with culture-positive samples having larger amounts of antigen and DNA compared to culture-negative samples. GM EIA and qPCR assay add to the sensitivity of BAL for diagnosing IPA in high-risk patients, with excellent specificity. Adjunctive use of these tests may reduce dependence on invasive diagnostic procedures.